Effectiveness of debriefing towards healthcare professionals’ nontechnical skills: a critical review - Muhamad Nur Fariduddin Abdul Aziz; Wee, Lei Hum; Lilia Halim; Mohd Johar Jaafar (Penerbit Universiti Kebangsaan Malaysia, 2018)
The importance of nontechnical skills among healthcare professionals is gaining widespread recognition as critical elements complementing technical skills that are used to improve patients’ safety. These skills are typically acquired through simulation training which has emerged as an effective way to complement clinical training. Effective simulation requires structure and effective debriefing methods to enhance its learning outcome. In previous literature, evidence of the effectiveness of healthcare simulation was available but studies evaluating debriefing method(s) remain sparse. In this paper, the effectiveness of debriefing methods in eight studies on the acquisition of nontechnical skills among healthcare professionals is reviewed. Articles published from 1st January 2016 across three different databases were referred to. The results of the review show a statistically significant improvement in the performance of nontechnical and technical skills across different professionals through various methods of debriefing. Nontechnical skills such as teamwork, effective communication, decision-making, and situational awareness have improved significantly. In addition, integration of realism in simulation learning has begun to emerge as an effective technique of providing a real world experience. However, there was lack of detailed information on the length and type of debriefing conducted in the studies. These methods clearly require further research since the key to successful simulation learning is through debriefing which is the heart of simulation.